Scholastic Tradition and Mesopotamian Law: A Study of FLP 1287, a Prism in the Collection of the Free Library of Philadelphia - Roth, Martha Tobi
PhD Diss.; Supervisors: Å. W. Sjöberg and B. Eichler. 371 p. Cf. DissAbstr 40 (1980) 5421-A.